2006
DOI: 10.1007/11618058_5
|View full text |Cite
|
Sign up to set email alerts
|

On Embedding a Cycle in a Plane Graph

Abstract: Consider a planar drawing Γ of a planar graph G such that the vertices are drawn as small circles and the edges are drawn as thin strips. Consider a cycle c of G. Is it possible to draw c as a nonintersecting closed curve inside Γ, following the circles that correspond in Γ to the vertices of c and the strips that connect them? We show that this test can be done in polynomial time and study this problem in the framework of clustered planarity for highly non-connected clustered graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, we will prove that a different reduction from (G, γ ) yields a flat clustered graph C(G, T ) whose cplanarity is in fact a necessary and sufficient condition for the strip planarity of (G, γ ); in other words, we will prove that the strip planarity testing problem reduces in polynomial time to the c-planarity testing problem for flat clustered graphs. Furthermore, it turns out that strip planarity testing coincides with a special case of a problem posed by Cortese et al [12,13] and related to c-planarity testing. The problem asks whether a graph G can be planarly embedded "inside" an host graph H , which can be thought as having "fat" vertices and edges, with each vertex and edge of G drawn inside a prescribed vertex and a prescribed edge of H , respectively.…”
Section: Strip Planarity and Clustered Planaritymentioning
confidence: 90%
“…However, we will prove that a different reduction from (G, γ ) yields a flat clustered graph C(G, T ) whose cplanarity is in fact a necessary and sufficient condition for the strip planarity of (G, γ ); in other words, we will prove that the strip planarity testing problem reduces in polynomial time to the c-planarity testing problem for flat clustered graphs. Furthermore, it turns out that strip planarity testing coincides with a special case of a problem posed by Cortese et al [12,13] and related to c-planarity testing. The problem asks whether a graph G can be planarly embedded "inside" an host graph H , which can be thought as having "fat" vertices and edges, with each vertex and edge of G drawn inside a prescribed vertex and a prescribed edge of H , respectively.…”
Section: Strip Planarity and Clustered Planaritymentioning
confidence: 90%
“…1(a)). It turns out that strip planarity testing coincides with a special case of a problem opened by Cortese et al [8,9] and related to c-planarity testing. The problem asks whether a graph G can be planarly embedded "inside" an host graph H, which can be thought as having "fat" vertices and edges, with each vertex and edge of G drawn inside a prescribed vertex and a prescribed edge of H, respectively.…”
Section: Introductionmentioning
confidence: 76%
“…• Cortese et al showed that the c-planarity testing and embedding problem is polynomial-time solvable for rigid clustered cycles, that is, for flat clustered graphs where the underlying graph is a cycle and the graph of the clusters' adjacencies is planar and has a fixed embedding [8].…”
Section: Introductionmentioning
confidence: 99%